Cover Feature: Lithium Difluorophosphate as an Effective Additive for Improving the Initial Coulombic Efficiency of a Silicon Anode (ChemElectroChem 18/2020). Issue 18 (24th August 2020) - Li, Chao; Zhu, Weicheng; Lao, Banggui; Huang, Xiangxuan; Yin, Huibin; Yang, Zhenyu; Wang, Hongyu; Chen, Deliang; Xu, Yongjun
Abstract : The Cover Feature illustrates the noticeable improvements of initial coulombic efficiency of the silicon anode after the addition of lithium difluorophosphate into the electrolyte. The improvement comes about by inhibiting lithium resources from participating in the film‐forming reaction. More information can be found in the Article by C. Li et al .